Comparative analysis of readability level of basic six pupils in private and public schools in Ibadanland (2015)
The study was carried out to determine the readability level of pupils in private and public primary schools in Ibadan land. The study used simple random sampling with a sample size of 109 participants from both private and public basic six pupils from three selected local government areas in Ibadan land. Sixty-four pupils were taken from public schools while 45 pupils were selected from private schools. Modular English Course for Primary Schools Book Six was used to assess the readability level of the pupils. SMOG index and Close test procedure were used to measure the readability levels of the pupils. The data collected were analysed using the simple percentages to classify the participants into different readability levels and t-test statistics was used for comparison between readability levels of the pupils. The results indicated that the pupils from private primary school had readability levels of 78% independent, 22 % instructional, and 0% at frustration level, while the pupils from public schools had 31% at independent level, 36% at instructional level and 33% at frustration level respectively. The Smog index test is 5.82. There is significant difference in readability level of the basic six pupils in private and public schools (t = 6.294, df = 307 and p<0.05). Suggestions were made concerning low performance of public primary school pupils compared to their counterparts from private schools. This study-recommends another or closer look at the English textbooks in use in schools in Ibadan land. Also, it is recommended that Government should employ experts in English language to handle the teaching-learning of English language right from the primary school level in enhancing the reading culture of the in-coming generation.